PENGARUH KUALITAS AUDITOR TERHADAP TEMUAN AUDIT DENGAN TINDAK LANJUT REKOMENDASI HASIL PEMERIKSAAN SEBAGAI VARIABEL INTERVENING (STUDI PADA INSPEKTORAT PROVINSI SULAWESI TENGGARA) - Dharmawati, Tuti; Yusran, Indha Novitasari (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
ABSTRACTThis study aimed to determine the effect of auditor quality on the audit findings through the follow-up of audit recommendations as an intervening variable. The sample in this study are all of functional apparatus in Inspectorate of Southeast Sulawesi Province with 23 people as observations. Data analysis method used path analysis of SPSS version 21.00.The results of this study showed that there was a direct and significant effect between 1) the auditor quality on the follow-up of audit recommendations, 2) the auditor quality on the audit findings, 3) the follow-up of audit recommendations on the audit findings. This study also showed that there was indirect effect between auditor quality on the audit findings through the follow-up of audit recommendations as an intervening variable. The total coefficient of determination showed that the contribution auditor quality on the audit findings through the follow-up of audit recommendations as an intervening variable was 95,3% , while the rest 4,7% obtained from the contribution of other factors. In other words, the contribution of the auditor quality on the audit findings through the follow-up of audit recommendations as an intervening variable considered as significant.Keyword : Auditor quality, audit findings, follow-up.